TEACHER EMPOWERMENT TOWARDS PROFESSIONAL DEVELOPMENT AND EFFECTIVENESS-CONCEPT, NEED AND IMPORTANCE - J. Nagabhooshanam, (EPRA International Journal of Research and Development (IJRD), 2022)
Generally Teaching is delivered by a teacher to enhance the amount of learning of a learner. To make learning more meaningful, understandable and fruitful to a learner, effectiveness of teaching delivered by a teacher is very essential condition. This concept of teaching-learning process is not exceptional one in case of development in teacher training institutions. Empowered teachers are given the encouragement and support necessary to take risks and engage in Continuous Professional Development (CPD) while collaborating with their colleagues and this process is essential to success in education. Being an empowered teacher means having enough resources and freedom to provide every student with the education that they deserve. The present paper deals in lime light the relationship among teacher empowerment, professional development and effectiveness.